Plant identification code: Learning media based on qr-code for plant exploration in P-WEC conservation area - Riantina Fitra Aldya; Anis Samrotul Lathifah; Suhartini (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2022)
Petungsewu Wildlife Conservation (P-WEC) is an informal education center on nature and wildlife conservation who has many wild plants to learn, but learning related to plants in the area is still not optimal due to the lack of tools that make it easier for visitors to learn plant exploration, also learning by biology students and visitors still not optimal because learning is still centered on the drawing sheet presented plants, so that independent exploration has not been widely carried out, so this research aims to determine the feasibility of the PIC (Plant Identification Code) as a learning media based on qr-code for plant exploration in P-WEC Conservation area. This research was used Research and Development (R&D) with ADDIE model which includes the analysis, design, development, implementation and evaluation stage. The data were collected using a questionnaire to measure the feasibility of media by media and material expert, and also visitor who are visitors who are biology students. The result showed that PIC Media are feasible to use with score of 4.10 and 3.85 (feasible) according to media and material experts, and also score of 4.22 (very feasible) according to the visitors who is Biology students. It is because the media can increase the efficiency in the learning environment where information related to plants can be accessed independently by students using a scanner application on android during exploration and plant identification learning in the P-WEC conservation area.